Pembangunan Aplikasi Pembelian Barangan Runcit Menggunakan Realiti Terimbuh - Jamaludin, Fatin Liyana; Ismail, Mohd Norasri (Applied Information Technology And Computer Science, 2021)
The Retail Grocery Shopping application using a augmented reality is a platform to facilitate consumers in the activity of purchasing groceries in the supermarket more quickly and easily because in this supermarket there is no price scanner on each shelf. In addition, this application was also developed because this supermarket still does not have an application that can be used by customers to shop at this supermarket. The objective of this project is to design and develop a mobile application using Augmented Reality (AR) technology and further test the functionality of the application on target consumers who shop at Econsave supermarkets. The process model used is Agile which has five phases and needs to be completed in sequence. In addition, this application is also developed using AR without markers (markerless) to track prices on scanned items. The results obtained as a result of consumer acceptance testing were 92.62%. Overall, these applications can be classified as applications that successfully meet the needs of target users.